STRATEGI OPTIMALISASI PEMBIAYAAN PADA PERGURUAN TINGGI MUHAMMADIYAH DI KABUPATEN PRINGSEWU LAMPUNG - Wulan Primanita Swastiyani; Suhendar Sulaeman; Andry Priharta (Taksasila Edukasi Insani, 2026)
This study addresses the critical issue of financial sustainability faced by Muhammadiyah Higher Education Institutions (PTM) in Pringsewu Regency, which heavily rely on student tuition fees (SPP) as their primary source of funding. The research aims to analyze the current financial structure, identify key challenges, and formulate effective, efficient, and applicable financing optimization strategies. Employing a qualitative approach with a case study method at Muhammadiyah University of Pringsewu (UMPRI), the study involves in-depth interviews with university leaders, finance managers, lecturers, students, and local Muhammadiyah board members. The data were thematically analyzed using NVivo software to reveal dominant themes in the financing system. The findings indicate that optimal financing strategies should focus on income diversification, budget efficiency, financial governance improvement, and strategic partnerships based on the triple helix model. This research highlights the importance of financial reform that leverages internal resources and promotes participatory external collaboration to ensure the sustainability and independence of Islamic-based higher education institutions in non-metropolitan areas like Pringsewu.Keywords: Financing Strategy, Muhammadiyah University of Pringsewu, Optimization, Sustainability, NVivo